Nurse managers’ knowledge and practices related to organizational citizenship behavior: cross–sectional survey: Nurses and Organizational Citizenship Behavior - Atalla, Amal Diab Ghanem; Zoromba, Mohamed A.; Mohamed, Samia Mohamed Sobhi (Acta Biomedica Atenei Parmensis, 2024)
Background: Organizational citizenship behavior (OCB) significantly influences employee performance, accounting for 63% of the variability. OCB’s importance is particularly pronounced in private healthcare settings, where it bridges operational gaps, facilitates effective communication, and nurtures loyalty and interpersonal harmony. The benefits of OCB are multifaceted, encompassing improved patient care, teamwork, employee engagement, and organizational efficiency, ultimately leading to cost reductions. Employees engaged in OCB tend to propose enhancements and innovative practices, thus mitigating process inefficiencies and superfluous expenses. Moreover, OCB plays a pivotal role in diminishing workplace conflicts, circumventing the need for expensive interventions and cultivating a congenial work environment. This research delves into the understanding and application of OCB among nurse managers. Methods: The study employed a cross-sectional survey methodology, executed at Mabert El Asafra East Hospital, Alexandria, Egypt. It encompassed all nurse managers (n=23) who met the eligibility criteria and consented to participate. Data collection hinged on two instruments: The Nurse Manager’s Knowledge about Organizational Citizenship Behavior Questionnaire and the Nurse Manager’s Practice of Organizational Citizenship Behavior Observational Scale. Results: The findings revealed that a substantial proportion of nurse managers (78.3%) possessed a comprehensive understanding of OCB, with the majority (82.6%) exhibiting proficient practice levels of the OCB model. Furthermore, a statistically significant linkage was observed between the nurse managers’ knowledge of OCB and their practical application of it, indicating a variance in the actual implementation and demonstration of OCB behaviors despite the presence of knowledge. Conclusion: The study underscored a robust and significant positive correlation between the overall knowledge of OCB and the implementation of its various dimensions, namely Altruism, Conscientiousness, Sportsmanship, Courtesy, and Civic Virtue, as perceived by the nurse managers.